THE PRACTICE OF ATTRACTING EXTRABUDGETARY FUNDING FOR HIGHER EDUCATION INSTITUTIONS - Alisher Bakberganovich Sherov (American Journals, 2024)
This research paper describes the content of financing of higher education institutions in Uzbekistan and foreign countries, sources of financing and the role of extra-budgetary funds in it. In addition, a comparative analysis of extra-budgetary funds, their composition and main indicators in the income of higher education institutions was conducted. During the study, an analysis was conducted using the methods of economic and statistical analysis, analysis and synthesis and corresponding conclusions were formed, as well as scientific proposals and practical recommendations for expanding the attraction of extra-budgetary funds to higher education institutions were developed.
Keywords: Education, higher education, budget expenditures, extra-budgetary funds, development fund, commercialization.